Encyclopedia of sleep - Kushida, Clete Anthony, 1960-; ScienceDirect eBooks (Amsterdam : Elsevier/Academic Press, 2013)
In a world of 24 hour media saturation, sleep has become an increasingly fraught enterprise. The 4-volume Encyclopedia of Sleep is the largest reference, either online or in print, on the subject of sleep. Written to be useful for the novice and the established researcher and clinician, Topic areas will include sleep across the life cycle and in other species, sleep and women, sleep and the elderly, pediatric sleep, sleep deprivation and loss, sleep mechanisms, sleep physiology and pathophysiology, sleep disorders, neurobiology, chronobiology, pharmacology, and impact of other disorders.
Basic Sleep Concepts, Science, Deprivation, and Mechanisms -- Assessment, Methodology, Training, and Policies of Sleep -- Circadian Rhythm Sleep Disorders (CRSD) -- Sleep Related Movement Disorders (SRMD) and Parasomnias.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Sleep -- Encyclopedias; Sleep disorders -- Encyclopedias; Sleep; Sleep Wake Disorders; HEALTH & FITNESS -- Sleep & Sleep Disorders; PSYCHOLOGY -- General; Sleep; Sleep disorders; Electronic books